Saturação venosa central e mista de oxigênio no choque séptico: existe diferença clinicamente relevante? - Machado, Flávia Ribeiro [UNIFESP] (2008)
INTRODUCTION: Central venous oxygen saturation (SvcO2) has been proposed as an alternative for mixed venous oxygen saturation (SvO2), with a variable level of acceptance according to available data. This study aimed to evaluate possible differences between SvO2 and SvcO2 or atrial venous saturation (SvaO2), with emphasis on the role of cardiac output and their impact on clinical management of the septic patient. METHODS: This is an observational, prospective study of patients with septic shock monitored by pulmonary artery catheter. Blood was obtained simultaneously for SvcO2, SvO2 and SvaO2 determination. Linear correlation (significant if p<0.05) and agreement analysis (Bland-Altman) were performed with samples and subgroups according to cardiac output. Moreover, agreement about clinical management based on these samples was evaluated. RESULTS: Sixty one measurements from 23 patients were obtained, median age of 65.0 (49.0-75.0) years and mean APACHE II of 27.7±6.3. Mean values of SvO2, SvcO2 and SvaO2 were 72.20±8.26%, 74.61±7.60% and 74.64±8.47%. Linear correlation test showed a weak correlation between SvO2 and SvcO2 (r=0.61, p<0.0001) and also between SvO2 and SvaO2 (r=0.70, p<0.0001). Agreements between SvcO2/SvO2 and SvaO2/SvO2 were -2.40±1.96 (-16.20 and 11.40) and -2.40±1.96 (-15.10 and 10.20), respectively, with no difference in the cardiac output subgroups. No agreement was found in clinical management for 27.8% of the cases, both for SvcO2/SvO2 and for SvaO2/SvO2. CONCLUSION: This study showed that the correlation and agreement between SvO2 and SvcO2 is weak and may lead to different clinical management.